Educational Values In The Children's Short Story Perkedel Sukun: A Pragmatic Study Of Children's Literature - Adellia Intan Maharani; Uum Qomariyah (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2026)
Background: Children's literature serves not only as entertainment but also as an effective medium for developing children's character through meaningful language use. However, studies examining speech acts in children's short stories from a pragmatic perspective remain limited, particularly in revealing how communicative functions convey character education values. Objective: This study aimed to identify the types of speech acts based on John Searle's speech act theory and to reveal the character education values embedded in Sarah Nafisah's children's short story Perkedel Sukun, published in Bobo magazine. Method: This study employed a descriptive qualitative approach using a pragmatic perspective. The data consisted of words, phrases, sentences, and dialogues containing speech acts in the short story. Data were collected through reading and note-taking techniques and analyzed by identifying, classifying, describing, and interpreting the speech acts according to Searle's classification. Results: The findings revealed that the short story is dominated by directive and representative speech acts. Directive speech acts appeared in the form of prohibitions, advice, and suggestions, while representative speech acts were expressed through statements, evaluations, and personal experiences. The analysis also identified several character education values, including sharing, cooperation, togetherness, caring, respect for others, and clean and healthy living habits. Novelty: This study integrates pragmatic speech act analysis with character education in children's literature, demonstrating how speech acts function as a medium for moral value transmission. Conclusion: The findings indicate that Perkedel Sukun is not only an entertaining literary work but also an effective educational resource for fostering positive character development among children through contextual language use.